Relationship between somatotype and physical fitness: Study on badminton athletes of PB Djarum Kudus - Nurlita Tri Ayuningtyas; Hardhono Susanto; Suroto Suroto (Jurnal Keolahragaan, 2021)
Badminton athletes should have good physical abilities supported by the suitability of body type (somatotype) as it affects their biomechanics in badminton and performance. The purpose of this study was to explore the correlation between Heath Carter somatotype component factors that affect physical fitness. This study was a cross-sectional research design was used with 43 athletes in PB Djarum Kudus who were selected purposively to be the respondents. The data on Heath Carter somatotype was obtained from anthropometric measurements to generate somatotype scores, namely endomorphy, mesomorphy, and ectomorphy. Cardiorespiratory endurance data were obtained using Balke test, power using vertical jump, and agility using court agility. The somatotype component types of all athletes are central (4.2-4.1-3). Male athletes are of central type (3.5-4-3.5) and females are of mesomorph-endomorph type (5-4-2). Both endomorphy and ectomorphy components showed significant correlation with cardiorespiratory endurance except mesomorphy component. Endomorphy component showed significant correlation with power except for mesomorphy and ectomorphy components. The ectomorphy component with a slender body shape with long arms and legs, low body fat percentage and strong muscle in the arms make it easier for badminton athletes to move in all positions combined.